Event Analogy for Privacy Preservation in Visual Surveillance - Yan, Wei Qi; Liu, Feng (Springer, 2015)
Privacy preservation as a thorny problem in surveillance has been arisen because of its relevance to human right, however it has not been completely solved yet today. In this paper, we investigate this existing problem and expect to get ride of those intuitive methods such as pixelization, blurring or mosaicking on human face regions through object tracking. We detail privacy preservation at event level and thereafter choose suitable events represented by motion pictures in virtual reality to replace those events of surveillance in real reality. The advantage of taking use of this approach is to leverage the utility and privacy of surveillance events. The outcome will not affect visual effects and surveillance security much however it is able to achieve the objectives of privacy preservation.
Keywords: Event analogy; Surveillance event; Privacy preservation; Real reality; Virtual reality